A new approach to educating conservators of Islamic manuscripts - Barkeshli, Mandana; Hepworth, Paul; Scheper , Karin (The ICOM CC Working Group for Education & Training, 2014)
Islamic manuscripts constitute a repository of enormous cultural and intellectual value and number in the millions. Yet currently there are no educational programs which focus on their specific conservation issues.